TELAAH HADIS KEPEMIMPINAN QURAISY MELALUI PENDEKATAN SOSIO-HISTORIS - Wildan Fatoni Yusuf; Hilmi Husaini Zuhri (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
Al-Mawardi listed the Quraish nasab as the seventh condition for the Ahl Imamah, which received many corrections from hadith scholars. The main reason is that the meaning of hadith is no longer relevant when it collides with current sociological realities. However, Al-Mawardi's argument is quite strong, because the majority of fuqaha simultaneously require that the highest leadership of the country must be of the Quraysh line. Therefore, this research answers this problem by examining the universal meaning in the Hadith and then contextualizing it. This research is included in library research whose methodological steps focus on interpretation using the asbabul wurud 'am approach (the cause of the decline of hadith at a macro level). The results of this research show that the hadith of the Quraish leadership which reads "al-Aimmatu min Quraishin" has a strong position as proof and evidence for the requirement of Imamah from the descendants of the Quraish. According to the majority of ulama, the scope of this hadith only focuses on the context of the highest leader of an Islamic state, not the area of ​​leadership whose political power is under the imamate of Zuma. Therefore, these hadiths tend to be technical and casuistic. However, the context of this hadith shows that the Quraysh had great power and influence. Leadership which has a strong influence in society is ultimately implemented in the leadership model in Indonesia.